ON THE GF-VALUES FOR SOME DIATOMIC MOLECULAR SPECTRA - Kuznetsova, L. A.; Shavrina, A. V. (Одеські астрономічні публікації, 2017)
In view of rich structure of the energy levels and the variety of transition types which are observable, molecules are the useful tool for investigation of physical parameters of stellar atmospheres, interstellar and circumstellar matter. such as gas density, its temperature, chemical and isotopic composition, ionization degree, radiation field density, kinematics, etc. The success of investigations is defined to a considerable extent by the amount and reliability of spectral information used. The molecular radiative coefficients must be calculated for a huge number of spectral lines, involving rather weak lines. These calculations are performed using spectral line lists containing such parameters as positions of line centres, lower level energies, transition probabilities, and, in a number of cases, broadening parameters.